Intergenerational Divide: Can One Motivational Approach Drive Them All? - Viržintaitė-Banienė, Eglė (Vilnius University Proceedings, 2023)
In the past decade, Human Resource professionals have faced an increasing challenge in dealing with issues related to intergenerational divide in the workplace, as four different cohorts coexist. This divide is influenced by a variety of factors such as increased life expectancy, rapidly evolving technologies, the era of social networks, declining demographics, and many others. Moreover, the turbulences in the world over the last few years, such as the Global pandemic, have only highlighted existing problems and presented additional challenges. Motivating employees is inherently a complex issue, and dealing with generational differences becomes even more so. Due to that, organizations, their HR professionals, and managers are confronted with the question of whether it is possible to create a single motivational system for employees of all generations, or whether a tailor-made approach is needed. Even though it is nearly impossible to answer the mentioned question unequivocally, the goal, while writing this article, was at least to move towards the point of better understanding. After analysing multiple studies carried out by various scholars, as well as research papers, not only generational differences were touched upon, but also similarities in the context of motivation. Moreover, four motivation drives were characterized, which, as it turned out, correlate quite closely with the main similarities of cohorts in the context of motivation